2022
DOI: 10.3389/fonc.2022.1027792
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, biological characterization and preliminary human imaging studies of 68Ga-DOTA-IBA

Abstract: PurposeIn this study, DOTA-IBA was radiolabeled with 68Ga and we determined the optimum labelling conditions and assessed the biological properties of 68Ga-DOTA-IBA. We investigated the biodistribution of 68Ga-DOTA-IBA in normal animals and undertook PET/CT imaging in humans. Finally, we explored the feasibility 68Ga-DOTA-IBA as a bone imaging agent and demonstrated its potential for the therapeutic release of 177Lu/225Ac-DOTA-IBA.MethodsThe controlled variables method was used to assess the impact of variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 19 publications
1
22
0
Order By: Relevance
“…Patients had received surgery, radiotherapy, chemotherapy, endocrinotherapy, immunotherapy, targeted therapy, or diphosphonate as previous treatments and were on palliative treatment with no other treatment options available or unwilling to accept other treatments except for 177 Lu-DOTA-IBA at the time of inclusion. Adequate bone marrow function, including a hemoglobin level of more than 60 g/L, total leukocyte counts greater than 2.5 × 10 9 /L, and platelet counts greater than 60 × 10 9 /L, was required for eligibility. Estimated life expectancy had to be at least 3 months.…”
Section: Methodsmentioning
confidence: 99%
“…Patients had received surgery, radiotherapy, chemotherapy, endocrinotherapy, immunotherapy, targeted therapy, or diphosphonate as previous treatments and were on palliative treatment with no other treatment options available or unwilling to accept other treatments except for 177 Lu-DOTA-IBA at the time of inclusion. Adequate bone marrow function, including a hemoglobin level of more than 60 g/L, total leukocyte counts greater than 2.5 × 10 9 /L, and platelet counts greater than 60 × 10 9 /L, was required for eligibility. Estimated life expectancy had to be at least 3 months.…”
Section: Methodsmentioning
confidence: 99%
“…225 Ac-based prostate-specific membrane antigen–targeted therapy and peptide receptor radionuclide therapy are emerging as the promising new modalities for the treatment of metastatic castration-resistant prostate cancer 9,10 and neuroendocrine tumor 11–13 . DOTA-IBA is new a precursor targeting bone metastasis, which can be used for radionuclide labeling with 68 Ga, 177 Lu, and 225 Ac for the diagnosis or treatment of bone metastasis 1,2 . This case showed 225 Ac-DOTA-IBA has a satisfactory therapeutic efficacy in the treatment of bone metastasis.…”
mentioning
confidence: 89%
“…This study has been approved by the ethics committee of The Affiliated Hospital of Southwest Medical University (KY2022114). Before treatment, she underwent 68 Ga-DOTA-IBA (a new tracer for evaluating bone metastasis 1,2 ) PET/CT imaging. Maximum intensity projection ( A ), axial PET ( B – D) , fused ( E – G ), and CT images ( H – J ) showed multiple bone destruction with increased tracer uptake.…”
mentioning
confidence: 99%
“…Preclinical studies of 68 Ga/ 177 Lu-DOTA-IBA showed high hydroxyapatite binding, good target-to-background ratio, and rapid renal clearance, providing a set of potential diagnostic and therapeutic integrative radiopharmaceuticals. 1,3 Our case showed 177 Lu-DOTA-IBA is a promising therapeutic option for the treatment of bone metastasis in prostate cancer, but more studies and experiments are needed.…”
mentioning
confidence: 90%
“…ChiCTR2200064487). Before treatment, he underwent PET/CT imaging with 68 Ga-DOTA-IBA (a new tracer for evaluating bone metastasis [1][2][3] ). Maximum intensity projection (A) image showed multiple elevated tracer uptake in the whole body bones.…”
mentioning
confidence: 99%